SAT-317 The Importance of Accurate Genetic Diagnosis Highlighted in a Case of Recurrent Bilateral Pheochromocytomas - Choo, Kuan Swen (J Endocr Soc, 2019)
Background It is estimated that one-third of patients with pheochromocytomas and paragangliomas (PPGL) have germline mutations. This patient with bilateral pheochromocytomas was initially diagnosed with MEN2A syndrome, underwent prophylactic total thyroidectomy, only to be diagnosed with a different germline mutation subsequently. Clinical case This patient first presented at 12 years of age, with hypertensive emergency and a right 8cm adrenal tumour with spontaneous haemorrhage. He underwent emergency right adrenalectomy, with histology confirming a pheochromocytoma. Post-operatively, urinary metanephrines were normal and symptoms resolved. 7 years later, he re-presented with headache, postural hypotension, cutaneous lichen amyloidosis and elevated urinary normetanephrine (NMT). CT abdomen showed 2 left adrenal masses with no residual right adrenal lesion. Open left adrenalectomy was performed and 3 pheochromocytoma nodules of 8 to 10mm in size were found. Urinary NMT was normal post-surgery. He was commenced on hydrocortisone and fludrocortisone replacement. In view of his young age and bilateral pheochromocytomas, genetic testing was done. RET proto-oncogene testing showed a silent mutation in Exon 13 Codon 769 CTT->CTG coding for Leucine, suggestive of MEN2A syndrome. His calcium and parathyroid hormone were normal. Although asymptomatic, he underwent prophylactic total thyroidectomy. However, histology revealed no endocrine cell hyperplasia. At age of 33 years, his symptoms recurred. Plasma free NMT was raised, 3.29nmol/L (reference <0.71nmol/L), while plasma metanephrine and 3-methoxytyramine were normal. Ga68-DOTAPEPTIDE PET/CT showed one tracer-avid lesion in each adrenal bed, suspicious of recurrent bilateral disease. He underwent open bilateral adrenalectomy and histology confirmed bilateral recurrent pheochromocytomas. Post-operatively, his plasma NMT has normalised. His atypical presentation for MEN2A syndrome prompted a repeat hereditary PPGL genetic testing. A pathogenic variant in the SDHD gene, namely c.3G>C (Initiator codon) was identified, while his previous MEN2A mutation of indeterminate significance was deemed not pathogenic. His father subsequently tested positive for SDHD mutation and is undergoing further investigations. Conclusion Major advances in the understanding of hereditary PPGL have been made over the last decade. Identification of the correct germline mutation is important to predict risks of malignancy, recurrence and guide early treatment. This case highlights the importance of comprehensive, targeted genetic testing with trained geneticist over traditional single gene tests and the need to interpret results with caution. Reference Pheochromocytoma and Paraganglioma: An Endocrine Society Clinical Practice Guideline. Jacques W.M. Lenders et al. J Clin Endocrinol Metab.2014; 99 (6): 1915-1942.